2013
DOI: 10.1111/jcmm.12119
|View full text |Cite
|
Sign up to set email alerts
|

Berberine potently attenuates intestinal polyps growth in ApcMin mice and familial adenomatous polyposis patients through inhibition of Wnt signalling

Abstract: As a traditional anti-inflammatory Chinese herbal medicine, Alkaloid berberine has been recently reported to exhibit anti-tumour effects against a wide spectrum of cancer. However, the mechanism was largely unknown. Gene chip array reveals that with berberine treatment, c-Myc, the target gene of Wnt pathway, was down-regulated 5.3-folds, indicating that berberine might inhibit Wnt signalling. TOPflash analysis revealed that Wnt activity was significantly reduced after berberine treatment, and the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…A concentration dependent decline in the cell survival has been observed in various prostate cancer cells treated with berberine [37]. A similar effect has been observed earlier in SNU-5, human glioblastomaT98G and colon cancer KM12C, KM12SM and KM12L4A cells treated with berberine [38][39][40][41]. Berberine has been shown to induce DNA damage in Ehrlich ascites carcinoma cells [19].…”
Section: Discussionsupporting
confidence: 56%
“…A concentration dependent decline in the cell survival has been observed in various prostate cancer cells treated with berberine [37]. A similar effect has been observed earlier in SNU-5, human glioblastomaT98G and colon cancer KM12C, KM12SM and KM12L4A cells treated with berberine [38][39][40][41]. Berberine has been shown to induce DNA damage in Ehrlich ascites carcinoma cells [19].…”
Section: Discussionsupporting
confidence: 56%
“…Studies have demonstrated that phytochemicals are effective in modulating Wnt/ -catenin signalling pathway (Zhang, et al, 2013;Kim et al, 2014). Ellagic acid, a dimeric derivative of gallic acid occurs naturally in fruits as-strawberry, raspberry, pomegranate, grapes and blackberries and in nuts (Thresiamma and Kuttan, 1996;Talcott and Lee, 2002;Mullen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic defects triggering aberrant activation of Wnt/ -catenin signalling are common and are reported in over 90% of sporadic cases of colon cancer (Miyaki et al, 1994;Clevers, 2006;Klaus and Birchmeier, 2008;Schon et al, 2014). The key effecttor of Wnt/ -catenin signaling pathway is -catenin that upon activation of Wnt signal, translocates into the nuclear region forming a ternary complex with transcription factors-TCF/Lef (T-cell factor, lymphoid enhancer factor) and activates genes involved in cell pro- Studies have demonstrated that phytochemicals are effective in modulating Wnt/ -catenin signalling pathway (Zhang, et al, 2013;Kim et al, 2014). Ellagic acid, a dimeric derivative of gallic acid occurs naturally in fruits as-strawberry, raspberry, pomegranate, grapes and blackberries and in nuts (Thresiamma and Kuttan, 1996;Talcott and Lee, 2002;Mullen et al, 2003).…”
mentioning
confidence: 99%
“…Both ligustrazine and berberine are the component of Chinese herbs that have been used for more than two decades for the treatment of atherosclerotic and inflammatory diseases [26][27][28][29] . Our study demonstrated that ligustrazine alone improved cardiac function in CME rats, as evidenced by an increased +dp/dt max , decreased LVEDP, and decreased serum CK-MB level.…”
Section: Wwwchinapharcom Zhang Y Et Almentioning
confidence: 99%